Approaches to construct high-performance Mg–air batteries: from mechanism to materials design. Issue 15 (23rd March 2023) - Zhang, Jiahe; Zhang, Hanfang; Zhang, Yingge; Wang, Xuemei; Li, Hongfen; Feng, Feng; Wang, Ke; Zhang, Gaixia; Sun, Shuhui; Zhang, Yihe
Abstract : Critical Mg–air battery researches is reviewed on battery mechanisms and electrode materials. The effect of reaction characteristics on battery performance and the impact of energy storage mechanisms on material design are discussed with emphasis. Abstract : Magnesium–air (Mg–air) batteries exhibit very high theoretical energy output and represent an attractive power source for next-generation electronics and smart grid energy storage. In this review, the fundamental principles in the electrochemical reactions of Mg–air batteries are introduced, mainly focusing on the negative corrosion and positive catalytic mechanisms as well as their influence on electrode design. Then, a series of representative electrode materials are reviewed, from materials chemistry to electrode performance. Among these, the main points are to address the challenges faced by Mg–air batteries through electrode material design. Finally, the challenges in the development of Mg–air batteries and the prospects of research directions are presented. The outline of the energy delivery mechanism and strategies for materials construction can serve as a guide for the evolution of high-performance batteries.